Metabolic responses of primary and transformed cells to intracellular Listeria monocytogenes. - Nadine Gillmaier (Public Library of Science (PLoS), 2012)
The metabolic response of host cells, in particular of primary mammalian cells, to bacterial infections is poorly understood. Here, we compare the carbon metabolism of primary mouse macrophages and of established J774A.1 cells upon Listeria monocytogenes infection using (13)C-labelled glucose or glutamine as carbon tracers. The (13)C-profiles of protein-derived amino acids from labelled host cells and intracellular L. monocytogenes identified active metabolic pathways in the different cell types. In the primary cells, infection with live L. monocytogenes increased glycolytic activity and enhanced flux of pyruvate into the TCA cycle via pyruvate dehydrogenase and pyruvate carboxylase, while in J774A.1 cells the already high glycolytic and glutaminolytic activities hardly changed upon infection. The carbon metabolism of intracellular L. monocytogenes was similar in both host cells. Taken together, the data suggest that efficient listerial replication in the cytosol of the host cells mainly depends on the glycolytic activity of the hosts.